2010
DOI: 10.1136/jnnp.2010.223479
|View full text |Cite
|
Sign up to set email alerts
|

No association of abnormal cranial venous drainage with multiple sclerosis: a magnetic resonance venography and flow-quantification study

Abstract: Findings suggestive of anomalies of the cranial venous outflow anatomy were frequently observed in both MS patients and healthy controls. Given the normal intracranial venous flow quantification results, it is likely that these findings reflect anatomical variants of venous drainage rather than clinically relevant venous outflow obstructions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
108
0
5

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(122 citation statements)
references
References 18 publications
9
108
0
5
Order By: Relevance
“…Patients with MS were autonomously seeking treatment at the department of cardiovascular and thoracic surgery of Onze-Lieve-Vrouw Ziekenhuis Aalst for so-called chronic cerebrospinal venous insufficiency syndrome, which is presumed to be caused by stenoses or obstructions of the internal jugular and/or azygos veins (12). However, jugular vein stenoses can also be found in healthy individuals (13). Patients with MS with internal jugular vein stenosis detected by CT venography were scheduled at their own explicit request for angioplasty.…”
Section: Resultsmentioning
confidence: 99%
“…Patients with MS were autonomously seeking treatment at the department of cardiovascular and thoracic surgery of Onze-Lieve-Vrouw Ziekenhuis Aalst for so-called chronic cerebrospinal venous insufficiency syndrome, which is presumed to be caused by stenoses or obstructions of the internal jugular and/or azygos veins (12). However, jugular vein stenoses can also be found in healthy individuals (13). Patients with MS with internal jugular vein stenosis detected by CT venography were scheduled at their own explicit request for angioplasty.…”
Section: Resultsmentioning
confidence: 99%
“…Similar prevalence rates of CCSVI in this MR imaging substudy were found, as in the previous study. 13 A number of recent reports have presented evidence against the CCSVI hypothesis in MS. [18][19][20][21][22][23][24][25][26][27][28][29] The possible reasons for the discrepancies in findings between different studies are numerous. 30 Veins have a tendency to collapse and change their morphology and size.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8] Some recent studies were able to partially reproduce original findings [2][3][4] with substantially lower sensitivity and specificity for MS, 9-17 while others were not able to support these findings using various imaging techniques. [18][19][20][21][22][23][24][25][26][27][28][29] In the CTEVD study, 13 the largest case-control study, to date, to investigate the prevalence of CCSVI in patients with MS, CIS, and other neurologic diseases, and HCs using specific proposed Doppler sonography criteria, 3 increased prevalence of CCSVI in MS was shown but with modest sensitivity and specificity. Despite the currently ongoing debate about whether CCSVI is associated with MS or not, 30 its significance in relation to MR imaging parameters also needs to be determined, both in patients with MS and HCs.…”
mentioning
confidence: 99%
“…Doepp and colleagues found no evidence of CCSVI in patients with MS using Doppler criteria [Doepp et al 2010]. Using magnetic resonance venography (MRV) and flowquantification study, Wattjes and colleagues found no evdience of venous back flow in patients with MS, and no difference between patients with MS and controls in terms of outflow abnormalities [Wattjes et al 2010]. Lastly, in a case control study, Sundströ m and colleagues found no differences in internal jugular venous outflow, aqueductal cerebrospinal fluid flow, or the presence of internal jugular blood reflux in patients with MS [Sundstrom et al 2010].…”
Section: Subsequent Studiesmentioning
confidence: 99%